Correction: Correction: Semaphorin 3D inhibits proliferation and migration of papillary thyroid carcinoma by regulating MAPK/ERK signaling pathway - Rui Hai; Qian You; Fei Wu; Guochun Qiu Qian; Yang Liang; Shu Linjun Xie; Xiangyu Zhou; Guochun Qiu; Qian Yang; Liang Shu; Linjun Xie (Molecular Biology Reports, 2026)

Correction: Semaphorin 3D inhibits proliferation and migration of papillary thyroid carcinoma by regulating MAPK/ERK signaling pathway - Rui Hai; Qian You; Fei Wu; Guochun Qiu; Qian Yang; Liang Shu; Linjun Xie; Xiangyu Zhou (Molecular Biology Reports, 2026)

Urbanization-induced cropland intensification and fragmentation result in threshold responses in soil antibiotic contamination - Linjun Shen; Liding Chen; Kaifeng Yang; Honglin Liu; Fangkai Zhao (Environmental Pollution, 2026)

Antipyretic pharmaceuticals intensify sewer H2S accumulation linked to biofilm matrix remodeling and altered sulfur metabolic potential - Linjun Li; Zhiqiang Zhang; Heliang Pang; Jing Yang; Yiwen Liu; Jinsuo Lu (Journal of Hazardous Materials, 2026)

Laboratory to bench-scale performance evaluation of a biphasic solvent for low-concentration CO2 capture from simulated gas turbine flue gas - Hang Yu; Sining Kong; Wenrui Li; Yitao Gan; Lijian Jin; Ruiyang Gao; Fan Zhang; Linjun Yang (Chemical Engineering Journal, 2026)

Waste heat recovery from flue gas inside MEA-based CO2 capture processes using heat pump technologies and associated environmental impact assessment - Lijian Jin; Debo Li; Lingxiao Zhan; Hang Yu; Wenrui Li; Yitao Gan; Sining Kong; Ruiyang Gao; Jinjin Li; Heng Chen; Linjun Yang (Journal of Cleaner Production, 2026)

Triple synergistic effects in biphasic solvents enable efficient CO2 capture from combined cycle gas turbines - Hang Yu; Lijian Jin; Wenrui Li; Sining Kong; Yitao Gan; Jinjin Li; Heng Chen; Fan Zhang; Linjun Yang (Chemical Engineering Journal, 2026)

Highly efficient hydrogen production via photothermal-catalytic methanol steam reforming over high-entropy metal oxides - Xingyu Yin; Linjun Tang; Zhiwei Zhan; Chun Zhu; Jingtai Zhang; Xiaoxiang Zhou; Shaohua Chen; Chuanyun Yang; Ling Li; Tetsuya Kako; Jinhua Ye; Shangbo Ning (Science Bulletin, 2026)

Unraveling emission characteristics and mitigation strategies for aerosols in a water-lean aromatic amine CO2 capture system - Wenrui Li; Heng Chen; Lijian Jin; Hang Yu; Yitao Gan; Hao Wu; Linjun Yang (Chemical Engineering Journal, 2026)

Absorption kinetics and interpretable machine learning model prediction based on aromatic amines/alkanolamines biphasic solvents - Lijian Jin; Xueyan Hou; Lingxiao Zhan; Hang Yu; Danping Pan; Wenrui Li; Yitao Gan; Sining Kong; Heng Chen; Jinjin Li; Linjun Yang; Dongping Zhang (Journal of Environmental Chemical Engineering, 2026)

Free radical mechanisms of halogen coexistence promoting pollutants formation - Mingxuan Wang; Shuting Liu; Linjun Qin; Qingyu Guo; Guorui Liu; Dong Cao; Lili Yang; Minghui Zheng (Journal of Environmental Sciences, 2026)

QDs fluorescent immunosensor based on magnetic separation coupled with machine learning for aflatoxin B1 detection in vegetable oils - Linjun Huang; Shixiang Zhang; Xiaofang Wang; Weining Wang; Fuming Yang; Dianyu Yu; Liqi Wang (Food Chemistry, 2025)

Aerosol emission characteristics of amine-based CO2 absorption systems: Influence of flue gas components and operating parameters - Wenrui Li; Heng Chen; Lijian Jin; Hang Yu; Yitao Gan; Hao Wu; Linjun Yang (Chemical Engineering Journal, 2025)

Non-aqueous biphasic absorbents for low-concentration CO2 capture: Achieving low viscosity, high cycling stability and energy efficiency in combined cycle gas turbine applications - Hang Yu; Lijian Jin; Wenrui Li; Sining Kong; Yitao Gan; Fan Zhang; Heng Chen; Jinjin Li; Linjun Yang (Chemical Engineering Journal, 2025)

Desulfurization wastewater evaporation for zero liquid discharge: Water and chloride balance in coal-fired power plants - Heng Chen; Hang Yu; Dayang Liang; Ziyan Yu; Liliang Lin; Ning Zhao; Linjun Yang (Journal of Water Process Engineering, 2025)

Persistent free radicals in the environment - Linjun Qin; Wuyuxin Zhu; Lili Yang; Minghui Zheng; Guorui Liu (Journal of Hazardous Materials, 2025)

Polyamidoamine modified magnetic carbon nanotubes for enzyme immobilization and its application to rice bran oil deacidification - Dianyu Yu; Yaguang Wang; Linjun Huang; Ning Wang; Tong Wang; Weining Wang; Fuming Yang (Food Bioscience, 2025)

Radical inhibition mechanisms of ammonium sulfate on industrial organic pollutants in copper-catalyzed reactions - Shuting Liu; Guorui Liu; Mingxuan Wang; Linjun Qin; Qingyu Guo; Da Li; Lili Yang; Minghui Zheng (Journal of Environmental Chemical Engineering, 2025)

Polyaluminium chloride surprisingly facilitated microbial activity in sludge biodrying through EPS solubilization - Benqin Yang; Linjun Feng; Yanqing Zhao; Yongli Wen; Lijuan Yin; Zhirong Xu; Hongyang Zhai; Qian Yang; Hao Yang; Xuejun Pan; Wei Jin (Journal of Environmental Chemical Engineering, 2025)

Source apportionment of polychlorinated dibenzo-p-dioxin/furans and polychlorinated biphenyls in soil from the Gyirong Valley in the Himalayas - Qingyu Guo; Mingxuan Wang; Yujue Yang; Guorui Liu; Qiuting Yang; Linjun Qin; Lili Yang; Minghui Zheng (Environmental Pollution, 2025)

Enhancing sulfide mitigation via the synergistic dosing of calcium peroxide and ferrous ions in gravity sewers: Efficiency and mechanism - Zhiqiang Zhang; Xiaowei Ren; Yuxin Liu; Shanshan Song; Yating Ren; Linjun Li; Heliang Pang; Jing Yang; Jinsuo Lu (Journal of Hazardous Materials, 2025)

Construction of a reaction-based fluorescent sensor for tandem detection of Cu2+ and glutathione in wine - Han Yang; Renqiang Chen; Linjun Dai; Boquan Ren; Feng Yang; Yan-Jun Xu; Qing Li (Food Chemistry, 2025)

Dual protonation reactions in biphasic absorbents facilitate efficient capture of low-concentration CO2 from gas-fired power plants - Hang Yu; Lijian Jin; Hangqi Yang; Wenrui Li; Shudan Chi; Fan Zhang; Heng Chen; Linjun Yang (Chemical Engineering Journal, 2025)

LSTM-GCN based multidimensional parameter relationship analysis and prediction framework for system level experimental bench - Linjun Yang; Zhuang Miao; Tong Li; Sichao Tan; Bo Wang; Dongyang Li; Yongchao Liu; Hengyuan Wei; Jiajun Li; Jiangkuan Li; Jiming Wen; Zhao Xu; et al. (Annals of Nuclear Energy, 2025)

Investigation on the rotary atomization evaporation of high-salinity desulfurization wastewater: Performance and products insights - Yurui Wang; Lingxiao Zhan; Qiwei Luo; Heng Chen; Juecen Mao; Jun Wan; Chaozhen Liu; Haijie Chen; Suoqi Zheng; Zhanxing Chen; Zhihao Li; Linjun Yang (Journal of Environmental Management, 2024)

Linking industrial emissions and dietary exposure to human burdens of polychlorinated naphthalenes - Yujue Yang; Cui Li; Lili Yang; Hao Zhu; Zhiyong Xie; Jerzy Falandysz; Roland Weber; Linjun Qin; Guorui Liu (Science of The Total Environment, 2024)

Free radical mechanisms of ammonium sulfate as intensively used industrial materials on suppressing organic pollutants - Shuting Liu; Guorui Liu; Mingxuan Wang; Linjun Qin; Qingyu Guo; Da Li; Lili Yang; Minghui Zheng (Science of The Total Environment, 2024)

SO3 removal by submicron absorbents synthesized via inhibition method: The product layer grows like parallel peaks - Hang Yu; Chengpeng Wang; Heng Chen; Chuanjia Shan; Jiaxing Sun; Wenlin Hang; Linjun Yang (Journal of Hazardous Materials, 2024)

Formation of persistent free radicals from epigallocatechin Gallate in tea processing and their implications on DNA damage and cell cytotoxicity - Linjun Qin; Lili Yang; Manabu Shiraiwa; Francesco Faiola; Yujue Yang; Shuting Liu; Guorui Liu; Minghui Zheng; Guibin Jiang (Food Chemistry, 2024)

Alkaline absorbents for SO2 and SO3 removal: A comprehensive review - Hang Yu; Chuanjia Shan; Jinjin Li; Xueyan Hou; Linjun Yang (Journal of Environmental Management, 2024)

Dynamic intrauterine crosstalk promotes porcine embryo implantation during early pregnancy - Xupeng Zang; Shengchen Gu; Wenjing Wang; Junsong Shi; Jianyu Gan; Qun Hu; Chen Zhou; Yue Ding; Yanjuan He; Lei Jiang; Ting Gu; Zheng Xu; et al. (Science China Life Sciences, 2024)

Analysis of the changes in the absorption and regeneration performance of diethylenetriamine in carbon capture environments with functionalized alcohols and mixed amines - Lijian Jin; Xueyan Hou; Lingxiao Zhan; Dawei Hou; Lina Gu; Daguang Zhang; Jianchong Shen; Zhihao Zheng; Chao Lv; Shaoqing Liu; Linjun Yang (Fuel, 2024)

Fe-doped CeTiOx catalysts facilitate the oriented oxidation of NO to achieving simultaneous desulfurization and denitration in a WFGD system - Lei Zhou; Zhixiang Wei; Junkang Fan; Qingqing Yu; Chuang Zhao; Jie Zhang; Liming Yang; Weili Dai; Linjun Yang (Fuel, 2024)

Occurrence states and migration of water during the evaporation of desulfurization wastewater - Lingxiao Zhan; Dawei Hou; Heng Chen; Yurui Wang; Suoqi Zheng; Zhihao Li; Hao Wu; Haijie Chen; Xiaoyue Ma; Linjun Yang (Desalination, 2024)

Design and synthesis of novel factor XIa Inhibitors with bicyclic isoquinoline and naphthalene fragments - Yi Zhang; Linjun Dai; Yi Tan; Yongpeng Yu; Junhao Xing; Feng Yang; Boquan Ren; Yan-Jun Xu; Qing Li (Medicinal Chemistry Research, 2024)

Review on the impact of SO2 on VOCs oxidation: Mechanisms and anti-poisoning strategies - Chengpeng Wang; Xueyan Hou; Lijian Jin; Jinjin Li; Lina Gu; Linjun Yang (Fuel, 2024)

Capturing CO2 using novel nonaqueous biphasic solvent TMEDA/MEA/DMSO: Absorption and phase splitting mechanism - Lijian Jin; Xueyan Hou; Lingxiao Zhan; Shangzhi Xie; Lina Gu; Hangqi Yang; Xin Wang; Xinfeng Qian; Jianchong Shen; Linjun Yang (Chemical Engineering Journal, 2024)

Study on the evaporation performance of concentrated desulfurization wastewater and its products analysis - Yurui Wang; Lingxiao Zhan; Heng Chen; Juecen Mao; Haijie Chen; Xiaoyue Ma; Linjun Yang (Journal of Water Process Engineering, 2024)

The effects of boar seminal plasma extracellular vesicles on sperm fertility - Zhiqian Xu; Yanshe Xie; Changhua Wu; Ting Gu; Xianwei Zhang; Jie Yang; Huaqiang Yang; Enqin Zheng; Sixiu Huang; Zheng Xu; Zicong Li; Gengyuan Cai; et al. (Theriogenology, 2024)

Ammonia release characteristics during desulfurization wastewater evaporation: Mechanisms and implications - Heng Chen; Dawei Hou; Zhihao Li; Lingxiao Zhan; Lijian Jin; Suoqi Zheng; Yurui Wang; Hao Wu; Ning Zhao; Liliang Lin; Linjun Yang (Journal of Water Process Engineering, 2024)

Enhancing aerosol emission reduction in an ammonia-based WFGD system with tray implementation - Rongting Huang; Yichun Tao; Wanyi Chen; Lin Lei; Shihang Li; Linjun Yang (Fuel, 2024)

Fine mapping and analysis of candidate genes for qBT2 and qBT7.2 locus controlling bolting time in radish (Raphanus sativus L.) - Yueyue Jin; Xiaobo Luo; Yadong Li; Xiao Peng; Linjun Wu; Guangqian Yang; Xiuhong Xu; Yun Pei; Wei Li; Wanping Zhang (Theoretical and Applied Genetics, 2024)

Mechanistic insights into the leaching and environmental safety of arsenic in ceramsite prepared from fly ash - Bing Song; Zequan Liu; Chengming Li; Shiji Zhou; Linjun Yang; Zhiliang Chen; Min Song (Chemosphere, 2023)

Efficient separation of dyes using two-dimensional heterogeneous composite membranes - Fengchun Jia; Liu Yang; Liyue Sun; Dehao Yu; Yu Song; Yanxin Wang; Matt J. Kipper; Jianguo Tang; Linjun Huang (Water Research, 2023)

Application of apatite particles for remediation of contaminated soil and groundwater: A review and perspectives - Zhiliang Li; Yi Qiu; Dongye Zhao; Jian Li; Guanlin Li; Hui Jia; Daolin Du; Zhi Dang; Guining Lu; Xiaofei Li; Chengfang Yang; Linjun Kong (Science of The Total Environment, 2023)

CO2-assisted synthesis of graphitic resin-based activated carbon for ultrahigh selective adsorption of VOCs under humid conditions - Jinjin Li; Tangying Cheng; Hao Wu; Linjun Yang (Fuel, 2023)

Hydrophobic carbon with hollow and hierarchical porous structures for efficient VOCs removal from complex exhaust gases: Experiments and DFT calculations - Jinjin Li; Tangying Cheng; Hao Wu; Linjun Yang (Chemical Engineering Journal, 2023)

Superior pore size for enhancing the competitive adsorption of VOCs under high humid conditions: An experiment and molecular simulation study - Jinjin Li; Yin Yin; Tangying Cheng; Heng Chen; Linjun Yang; Hao Wu (Journal of Environmental Chemical Engineering, 2023)

Release and mobility characteristics of thallium from polluted farmland in varying fertilization: Role of cation exchange - Ying Huang; Dexin Wang; Junhong Jiang; Jian Gong; Yuxian Liu; Long Li; Linjun Kong; Yang Ruan; Hang Lv; Yongheng Chen; Zibiao Chen; Qi Liang; et al. (Journal of Hazardous Materials, 2023)

Competitive adsorption characteristics of VOCs and water vapor by activated carbon prepared from Fe/N-doped pistachio shell - Tangying Cheng; Jinjin Li; Xiuwei Ma; Linjun Yang; Lei Zhou; Hao Wu (Environmental Science and Pollution Research, 2023)

A demonstration project for desulfurization wastewater evaporation technology: Field test and performance analysis - Heng Chen; Dawei Hou; Lingxiao Zhan; Zhihao Li; Suoqi Zheng; Fei Li; Haijie Chen; Hao Wu; Linjun Yang (Journal of Water Process Engineering, 2023)

The fate of selenium in the desulfurization wastewater evaporation process: Migration mechanisms and risk analysis - Heng Chen; Zhihao Li; Lingxiao Zhan; Suoqi Zheng; Hao Wu; Linjun Yang (Chemosphere, 2023)

Effects of corner weight vectors on the performance of decomposition-based multiobjective algorithms - Linjun He; Auraham Camacho; Yang Nan; Anupam Trivedi; Hisao Ishibuchi; Dipti Srinivasan (Swarm and Evolutionary Computation, 2023)

Investigation of Vortex-Induced Vibration of Double-Deck Truss Girder with Aerodynamic Mitigation Measures - Gang Yao; Yuxiao Chen; Yang Yang; Yuanlin Zheng; Hongbo Du; Linjun Wu (Journal of Marine Science and Engineering, 2023)
The long-span double-deck truss girder bridge has become a recommend structural form because of its good performance on traffic capacity. However, the vortex-induced vibration (VIV) characteristics for double-deck truss girders are more complicated and there is a lack of related research. In this research, wind tunnel tests were utilized to investigate the VIV characteristics of a large-span double-deck truss girder bridge. Meanwhile, the VIV suppression effect of the aerodynamic mitigation measures was measured. Furthermore, the VIV suppression mechanism was studied from the perspective of vortex shedding characteristics. The results indicated that the double-deck truss girder had a significant VIV when the wind attack angles were +3° and +5°. The aerodynamic mitigation measures had an influence on the VIV response of the double-deck truss girder. The upper chord fairing and lower chord inverted L-shaped deflector plate played a crucial role in suppressing VIV. Numerical analysis indicated that vortex shedding above the upper deck or in the wake region may dominate vertical VIV, while vortex shedding in the wake region of the lower deck may dominate torsional VIV. The upper chord fairing and lower chord inverted L-shaped deflector plate disrupted the original vortex shedding pattern in both regions, thereby suppressing VIV. This research can provide a foundation for bridge design and vibration suppression measures for large-span double-deck truss girder bridges.

High-permeable graphene oxide/graphitic carbon nitride composite nanofiltration membrane for selective separation of dye and desalination - Liu Yang; Fengchun Jia; Zhaoge Juan; Dehao Yu; Liyue Sun; Yu Song; Yanxin Wang; Linjun Huang; Jianguo Tang (Journal of Environmental Chemical Engineering, 2023)

Multiplex single-cell droplet PCR with machine learning for detection of high-risk human papillomaviruses - Yizheng Huang; Linjun Sun; Wenwen Liu; Ling Yang; Zhigang Song; Xin Ning; Weijun Li; Manqing Tan; Yude Yu; Zhao Li (Analytica Chimica Acta, 2023)

Free radical mechanism of toxic organic compound formations from o-chlorophenol - Xiaoyun Liu; Guorui Liu; Shuting Liu; Linjun Qin; Bingcheng Lin; Mingxuan Wang; Lili Yang; Minghui Zheng (Journal of Hazardous Materials, 2023)

Release and migration of Hg during desulfurization wastewater evaporation process: Whole process evaluation by experimental and theoretical study - Heng Chen; Lingxiao Zhan; Hao Zhou; Zhihao Li; Jiawei Chen; Zongkang Sun; Hao Wu; Linjun Yang (Journal of Hazardous Materials, 2023)

New insight into scale inhibition during tea brewing: Ca2+/Mg2+ complexing and alkalinity consumption - Linjun Li; Jinsuo Lu; Heliang Pang; Zhiqiang Zhang; Jing Yang; Pengpeng Li; Xiaoyu Yan; Miaomiao Fan (Journal of Environmental Sciences, 2023)

Nitrogen-doped porous biochar for selective adsorption of toluene under humid conditions - Tangying Cheng; Ye Bian; Jinjin Li; Xiuwei Ma; Linjun Yang; Lei Zhou; Hao Wu (Fuel, 2023)

Experimental study on the treatment of desulfurization wastewater from coal-fired power plant by spray evaporation - Zongkang Sun; Ning Zhao; Yongxin Feng; Fengjun Liu; Chenjian Cai; Guangmin Che; Yaping Zhang; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Effect of nitrogen functional groups on competitive adsorption between toluene and water vapor onto nitrogen-doped spherical resorcinol-formaldehyde resin-based activated carbon - Jinjin Li; Tangying Cheng; Xiuwei Ma; Xueyan Hou; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Concentration of desulfurization wastewater using low-temperature flue gas and associated corrosion risk - Hao Zhou; Lingxiao Zhan; Heng Chen; Linjun Yang (Environmental Science and Pollution Research, 2022)

Semaphorin 3D inhibits proliferation and migration of papillary thyroid carcinoma by regulating MAPK/ERK signaling pathway - Rui Hai; Qian You; Fei Wu; Guochun Qiu; Qian Yang; Liang Shu; Linjun Xie; Xiangyu Zhou (Molecular Biology Reports, 2022)

Removal of Hg2+ from desulfurization wastewater by tannin-immobilized graphene oxide - Heng Chen; Fengjun Liu; Chenjian Cai; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

The adsorption properties of microporous activated carbon prepared from pistachio nut shell for low-concentration VOCs under low-medium temperatures - Tangying Cheng; Jinjin Li; Xiuwei Ma; Lei Zhou; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2021)

Combined impact of organic matter, phosphorus, nitrate, and ammonia nitrogen on the process of blackwater - Lanmiao Li; Linjun Wu; Lingxiao Yang; Chao Liu; Jun Li; Naiwen Li (Environmental Science and Pollution Research, 2021)

BpTCP7 gene from Betula platyphylla regulates tolerance to salt and drought stress through multiple hormone pathways - Huiyu Li; Hongmei Yuan; Fumei Liu; Jiayu Luan; Yang Yang; Li Ren; Linjun An; Jing Jiang (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

APOBEC3B and IL-6 form a positive feedback loop in hepatocellular carcinoma cells - Shuran Li; Xueyang Bao; Duowei Wang; Linjun You; Xianjing Li; Hongbao Yang; Jinsong Bian; Yun Wang; Yong Yang (Science China Life Sciences, 2017)

Pretreatment with lipopolysaccharide attenuates diethylnitrosamine-caused liver injury in mice via TLR4-dependent induction of Kupffer cell M2 polarization - Xianjing Li; Zhuo Wang; Yulian Zou; Ermei Lu; Jingjing Duan; Hongbao Yang; Qijin Wu; Xiaona Zhao; Yun Wang; Linjun You; Ling He; Tao Xi; et al. (Immunologic Research, 2015)

Dominant bacterial communities in the rumen of Gayals (Bos frontalis), Yaks (Bos grunniens) and Yunnan Yellow Cattle (Bos taurs) revealed by denaturing gradient gel electrophoresis - Jing Leng; Linjun Xie; Renjun Zhu; Shuli Yang; Xiao Gou; Shuai Li; Huaming Mao (Molecular Biology Reports, 2011)